The Use of Financial Spreads As Indicator Variables : Evidence for the U.K. and Germany - Davis, E.; Henry, S. (Washington, D.C. : International Monetary Fund, 1994)
There has been growing interest in the use of financial spreads as advance indicators of real activity and inflation. Empirical evidence is marshalled on a range of spreads when these are used in vector autoregressive models of the UK and German economies. It is found that they do have significant information, even after allowing for the effects of other influences upon macro-economic activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet